2020
DOI: 10.1088/1757-899x/987/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some mechanical properties of PMMA/silica/zirconia nanocomposite as a denture base material

Abstract: In this research, nanocomposites of poly(methyl methacrylate) (PMMA) and a mixture of nano silica (SiO2) and nano zirconia (ZrO2) were prepared in different weight percentages of the nano fillers to improve some of the properties of PMMA resin to be used as a denture base material. The nano filles were surface modified with a coupling agent and added to the PMMA in different amounts. Impact strength, transverse strength, hardness and roughness were tested for both control and experimental groups. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Zhen et al [33] and Balso et al [34] found that with an increase in silica nanoparticles from 0 to 5 wt.%, the tensile strength and elongation in the fracture of composites have been improved, and also the flexural strength and elastic modulus have been significantly increased. Fatalla et al [35], observed a slight increase in impact strength, transverse strength, and hardness for 5 wt. % of silica nanoparticles.…”
Section: Of 12mentioning
confidence: 93%
“…Zhen et al [33] and Balso et al [34] found that with an increase in silica nanoparticles from 0 to 5 wt.%, the tensile strength and elongation in the fracture of composites have been improved, and also the flexural strength and elastic modulus have been significantly increased. Fatalla et al [35], observed a slight increase in impact strength, transverse strength, and hardness for 5 wt. % of silica nanoparticles.…”
Section: Of 12mentioning
confidence: 93%
“…Acrylic sheets were used to make the plastic model pattern, which designed by using computer software (AutoCAD), and then cut by a computercontrolled laser cutting machine. The length, width, and thickness of the plastic models pattern utilized in mold fabrication were precisely designated according to the specifications needed for test (7) . Sequare shape (10 x 10 x 3 mm) specimens were prepared according to Berger et al 2006 (6) .…”
Section: Methodsmentioning
confidence: 99%
“…An increase in cross-linking density might also explain the increase in nanocomposite hardness, which makes the polymer stiffer and more resistant to penetration. (5). Friction and wear materials are a beneficial area of material development.…”
Section: Introductionmentioning
confidence: 99%